Kinerja Guru Dalam Implementasi Kurikulum Merdeka Pada Sekolah Penggerak SMA Darut Taqwa Purwosari Pasuruan - Alfian Arif, Muhammad; Bashofi, Ferdinan (Universitas Yudharta Pasuruan, 2024)
This study assesses the efficacy of Sociology teachers at DARUT TAQWA Purwosari High School, Pasuruan, in adopting the Merdeka Curriculum. Employing a descriptive qualitative research approach, the investigation focused on the teachers of Phase E and F in Sociology, as well as Curriculum Developers. Data collection was achieved through interviews, observations, and documentation methods. Findings indicate that teachers meticulously planned their lessons in alignment with the Merdeka Curriculum's guidelines, executed the learning process effectively, and carried out structured evaluations. Areas for improvement in the learning process were identified, including the need for a broader range of probing questions and greater clarity in assignments given to students. The implementation of the Merdeka Curriculum encompasses the Pancasila Learner Profile Strengthening Project, aimed at enhancing skills and deepening understanding of Pancasila values. Evaluations were performed using three distinct types of assessments. The insights garnered from this evaluation serve as a foundational reflection to enhance the quality of education.